2008
DOI: 10.1007/s10517-008-0156-9
|View full text |Cite
|
Sign up to set email alerts
|

Study of bipathic effect of haloperidol

Abstract: Parallel treatment with haloperidol and ultralow-dose haloperidol significantly increased the psychotropic neuroleptic effect of traditional doses of the drug under conditions of preliminary of simultaneous administration, which attests to a bipathic effect of this preparation. Combination of ultralow and therapeutic doses of haloperidol significantly reduced its cataleptogenic side effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…It was shown that modulating action of RAD of phenazepam significantly potentiated anxiolytic and anticonvulsant effects of therapeutic doses of phenazepam in Vogel conflict test and in rats with corazol-induced seizures, both after prior or simultaneous administration [16]. Combination of RAD of haloperidol and therapeutic doses of haloperidol significantly increased psychotropic neuroleptic effect of conventional doses of the drug administered preliminarily or simultaneously [17]. In addition, RAD of haloperidol served to reduce significantly cataleptogenic side effect of haloperidol.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that modulating action of RAD of phenazepam significantly potentiated anxiolytic and anticonvulsant effects of therapeutic doses of phenazepam in Vogel conflict test and in rats with corazol-induced seizures, both after prior or simultaneous administration [16]. Combination of RAD of haloperidol and therapeutic doses of haloperidol significantly increased psychotropic neuroleptic effect of conventional doses of the drug administered preliminarily or simultaneously [17]. In addition, RAD of haloperidol served to reduce significantly cataleptogenic side effect of haloperidol.…”
Section: Introductionmentioning
confidence: 99%
“…In a series of experiments, animals were co-administered a "high" (either a therapeutic or even toxic) dose of a common drug, such as prednisolone, haloperidol, phenazepam, diclofenac or cyclophosphamide, together with a "high dilution" of the same drug. The results showed that in the presence of its "high dilution", the activity of the drug was positively modified, enhancing pharmacological effects and reducing toxicity [37][38][39][40][41][42][43][44][45][46][47][48].…”
Section: "High Dilutions" Of Substancesmentioning
confidence: 99%